Mapping International Trade and Supply Chains for Humanitarian and Business Resilience to Atmospheric and Pandemic Disasters Method and Preliminary Findings for Puerto Rico - García, Maribel-Aponte; Alvarez, Carlos A. (Journal of Applied Business and Economics, 2021)
The study presents preliminary findings of a Pilot Project that identified alternatives to disruptions in international trade and supply chains in the face of atmospheric (hurricane Maria in 2017) and pandemic (COVID-19) disasters. It focused on four critical imports: water, humanitarian relief goods, solar photovoltaic products, and COVID-19 test reagents. The project proposed an alternative pathway and method to address disruptions: build an integrated database from Bill of Lading and import-export-related data organized by Harmonized Schedule Code. Data analyses were carried out based on the Harmonized Tariff Schedule code system, and an integrated database was generated for imports of the four products that Puerto Rico buys in the international market. Import Key data were analyzed based on the Bill of Lading, sector, companies that sell the product, location of countries where the products are sold, ports that can reach Puerto Rico, and contact information of the companies and suppliers. This information allows humanitarian organizations, SMEs and the government to identify alternative supply networks.